Plants that never ever bloom - Heller, Ruth, 1924- (New York : Grosset & Dunlap, 1984)
Brief rhyming text and illustrations present a variety of plants that do not flower but propagate by means of spores, seeds, and cones.
Ill. on lining papers.
Child Study Children's Book Committee.
Booklist.
3.0
K-3
Keywords: Cryptogams -- Juvenile literature; Gymnosperms -- Juvenile literature; Cryptogams; Gymnosperms; Plants; Botany -- Pictorial works; Stories in rhyme; Plants -- Folklore; Cryptogams; Gymnosperms; Plants